HEMODYNAMIC FACTORS DETERMINING IMMEDIATE RESPONSE OF LEFT ATRIAL PRESSURE REDUCTION ATTRIBUTED TO BALLOON MITRAL VALVOTOMY - Funjan, Mawada Mousa; Msayer, Kawthar H; Taha, Zaid Mohammed (Al-Nahrain Journal of Science, 2010)
Rheumatic mitral stenosis is a chronic cardiac disease that results in considerable anatomicaland functional alternations. Mitral stenosis (MS) is associated with elevated left atrial pressure(LAP). Balloon Mitral Valvuloplasty (BMV) is a proven modality in the treatment of mitral valvestenosis. The purpose of this study was to assess the success of balloon mitral Valvotomy via themeasurements of LAP and PAP before and after procedures and to determine the hemodynamicfactors that may influence reduction in mean LAP in patients with adequate relief of mitral valveobstruction after BMV.Twenty seven patients with moderate to severe mitral stenosis underwent cardiaccatheterization. Hemodynamic measurements were recorded at pre-valvuloplasty and after balloonvalvuloplasty. All patients were submitted to an echocardiography before BMV and the test wasperformed after the procedure to measure the mitral valve area. The results presented in this studywere based on analysis of changes in mean left atrial pressure (LAP) attributed to BMV procedurequartiles in a sample of 27 patients with MS. The study subjects were categorized into orderedcategories based on resulting quartiles of LAP change. The group with highest change includedthose in whom LAP was ( 18) mmHg after BMV, the second group with average responseincluded those in whom LAP was (17) to (7) mmHg after BMV, and third group with lowestresponse included those in whom LAP was ( 6) mmHg after BMV. The changes in mean LAPattributed to procedure showed a statistically significant linear correlation with mean (LAP) beforeBMV (r  0.712, p<0.001), and mean pulmonary artery pressure (PAP) before BMV had astatistically significant linear correlation with changes in mean LAP attributed to procedure(r  0.68, p < 0.001). By using receiver operator characteristic curve (ROC) can distinguish thebest homodynamic measurements before BMV that can be efficiently determine change in meanLAP attribute to BMV procedure. The (mean LAP and mean PAP) before the procedure (pretreatment)are an important contributing factors for determine the reduction in mean LAP attributedto BMV procedure.